ORGANIZING-METHODICAL ACTIVITIES OF PREVENTION OF «ATYPICAL PNEUMONIA» AT REPUBLIC OF ALTAI - L. V. Shchuchinov; I. V. Zarubin (Acta Biomedica Scientifica, 2020)
Necessary organizing, methodical and preventive work was conducted at Republic of Altai and the border passing point «Tashanta» due to epidemiological complications and dissemination of «atypical pneumonia» in foreign countries. It facilitates to prevent severe acute respiratory syndrome (SARS) importation to the territory of Republic of Altai.